2016
DOI: 10.1590/1807-1929/agriambi.v20n12p1118-1123
|View full text |Cite
|
Sign up to set email alerts
|

Storage of ‘umbu-cajá’ pulp powder produced by lyophilization

Abstract: A B S T R A C TThis work aimed to study the chemical and physical stability of 'umbu-cajá' powders produced by lyophilization during storage. 'Umbu-cajá' pulps formulated with different concentrations of gum arabic (10, 20 and 30%), previously frozen, were dehydrated in benchtop lyophilizer at -40 °C for 48 h and disintegrated to obtain the powder, which was stored in laminated packages for 180 days at ambient conditions, with physical, chemical and physico-chemical analyzes performed at the beginning and ever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
6
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 8 publications
1
6
0
1
Order By: Relevance
“…This phenomenon is in agreement with Santos et al (2016), who reported an increase in the moisture content of 'umbu-cajá' (Spondias spp.) pulp along the 180 days of storage under ambient conditions.…”
Section: Resultssupporting
confidence: 93%
See 4 more Smart Citations
“…This phenomenon is in agreement with Santos et al (2016), who reported an increase in the moisture content of 'umbu-cajá' (Spondias spp.) pulp along the 180 days of storage under ambient conditions.…”
Section: Resultssupporting
confidence: 93%
“…Conegero et al (2017) observed increase in the water's activity, evaluating the stability of 'mangaba' (Hancornia speciosa Gomes) powder along the 90 days of storage. Santos et al (2016) stored 'umbu-cajá' (Spondias spp.) powder and reported an increase in water activity along the storage.…”
Section: Journal Of Agricultural Studiesmentioning
confidence: 99%
See 3 more Smart Citations